THE RELATIONSHIP OF RECRUITMENT AND CAREER DEVELOPMENT ON EMPLOYEES COMPETENCY AND PERFORMANCE IN SOME SHARIA BANK IN ACEH - Yenni Novita; A Hadi Arifin; Eny Dameria; Rani Gesta Putri (Program Pascasarjana Universitas Negeri Jakarta, 2021)
The recruitment process and career development system have a significant relationship to improve competence and improve employee performance. This study is useful for analyzing how much influence recruitment and career development have on employee competence and performance. The object of study is at some Sharia Bank in Aceh. The sample in this study was 160 respondents. Meanwhile, the data were analyzed using the AMOS Structural Equation Modeling Program. The findings of the data analysis show that recruitment and career development have a positive and significant effect on employee competence and performance. Competence can partially mediate the relationship between recruitment and career development to improve employee performance. Findings The results of the study recommend improving the quality of the recruitment process and procedures to get employees who have knowledge, skills, and improve a transformative career development system so that the Bank's performance is healthier and develops a syar'i competency pattern so that it is able to renew its performance through collaboration with the recruitment team. career development team and competency assessment team, to find syar'i banking human resources.